Analisis Faktor Kepatuhan Penggunaan Alat Pelindung Diri (APD) di Instalasi Gizi pada Rumah Sakit X - Indira Halimatu Azzah Roh; Amalia Rahma (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Hospitals are healthcare institutions with a high risk of disease transmission and cross-contamination, both for patients and healthcare workers. One of the key measures to prevent nosocomial infections is the proper and consistent use of Personal Protective Equipment (PPE) by nutrition installation staff. This study aims to analyze the factors influencing PPE compliance in the Nutrition Installation of Hospital X. This research employed a descriptive quantitative design involving 7 nutrition staff members consisting of 5 food servers (71.43%) and 2 cooks (28.57%). Based on educational background, most respondents had senior high school education (85.71%), while 1 respondent (14.29%) had an elementary-level education. Regarding work experience, 6 respondents (85.71%) had worked for more than 5 years, and 1 respondent (14.29%) had less than 5 years of experience. The results showed that most respondents had good knowledge of PPE compliance (72.8%), while 27.1% demonstrated moderate knowledge. In terms of attitude, 68.8% showed good attitudes, and 32.2% showed moderate attitudes. These findings indicate that the nutrition installation staff at Hospital X have a good understanding of the importance of PPE in ensuring safety and hygiene. However, regular training, continuous supervision, and ergonomic improvement of PPE are still needed to maintain and improve consistent compliance.